Distribusi Tenaga Kesehatan Provinsi dan Status Indikator Kesehatan Nasional: Analisis Deskriptif dari Indonesia (Journal of Telenursing (JOTING), 2025)
This study aims to descriptively map the adequacy of six categories of primary health workers, doctors, nurses, midwives, pharmacists, nutritionists, and sanitarians in 34 provinces in Indonesia and to relate them to the achievement of three health indicators, namely the Maternal Mortality Rate (MMR), Infant Mortality Rate (IMR), and stunting prevalence. The method used is a descriptive analysis of secondary data from official government sources. The study results indicate that most provinces have not met national standards for the availability of health workers, especially in the categories of pharmacy, nutrition, and environmental health workers. In addition, most provinces still have MMR and IMR rates that exceed national standards and stunt prevalence above the national average. In conclusion, the adequacy of health workers quantitatively has not directly impacted the achievement of health indicators, so more attention is needed to aspects of quality, functional distribution, and cross-disciplinary collaboration. These findings fill the evidence gap at the subnational level and provide direction for health worker distribution policies based on regional needs. Keywords: Distribution of Health Workers, Health Indicators, Infant Mortality, Maternal Mortality, Stunting.